New breeding colony of the Peruvian Tern (Sternula lorata) in southern coast of Peru - Vizcarra, Jhonson K. (2022)
This note describes the existence of a new reproductive colony of Sternula lorata in Pampa El Palo, located in the district and province of Ilo, department of Moquegua. Between August 2016 and March 2017, 8 to 324 S. lorata were recorded and 12 active nests were found. The reproductive area comprises about 600 ha and is characterized by being an open area with sandy-type soil and the presence of shells. This species faces some anthropogenic threats in the area, such as the traffic of motorized vehicles, the passage of local fishermen and the presence of domestic dogs.